HUBUNGAN KEKUATAN OTOT KAKI DAN OTOT PERUT TERHADAP KETERAMPILAN SHOOTING PADA SISWA PESERTA EKSTRAKURIKULER FUTSAL SMP NEGERI 7 MUARO JAMBI - Muhammad Alfarezi; Hendri Munar; Grafitte Decheline (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to determine the relationship between leg muscle strength and abdominal muscle strength on shooting skills in futsal. This research is motivated by the lack of basic shooting techniques among students. Based on this background, the researcher conducted a study to analyze the correlation between leg and abdominal muscle strength with shooting skills. This study used a quantitative correlational method to explain the relationship between variables. The population of this study consisted of 23 students participating in the futsal extracurricular activities at SMP Negeri 7 Muaro Jambi. The research applied total sampling, making all 23 students the sample. The instruments used were a leg dynamometer, sit-up test, and target goal test. Data analysis utilized a correlation test with a 5% significance level. The results showed that: (1) There is a significant relationship between leg muscle strength and shooting skills, with a Pearson correlation test result of 0.979. (2) There is a significant relationship between abdominal muscle strength and shooting skills, with a Pearson correlation test result of 0.985. (3) This explains that if students have good leg and abdominal muscle strength when shooting, their shooting performance will improve.